2015
DOI: 10.1080/17461391.2015.1085097
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coffee and caffeine anhydrous on strength and sprint performance

Abstract: Caffeine and coffee are widely used among active individuals to enhance performance. The purpose of the current study was to compare the effects of acute coffee (COF) and caffeine anhydrous (CAF) intake on strength and sprint performance. Fifty-four resistance-trained males completed strength testing, consisting of one-rep max (1RM) and repetitions to fatigue (RTF) at 80% of 1RM for leg press (LP) and bench press (BP). Participants then completed five, ten-second cycle ergometer sprints separated by one minute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 54 publications
0
39
1
6
Order By: Relevance
“…Peak power output and mean power output were not significantly different during the trials in which caffeine or coffee was consumed when compared to the placebo and control trials. In contrast, Trexler et al [ 22 ] reported that caffeine and coffee ingestion improved sprint performance; however, a dose of 300 mg caffeine was ingested in this study and therefore participants will have consumed differing amounts of caffeine relative to their body mass. Similarly, Hodgson, Randell and Jeukendrup [ 21 ] observed that coffee and caffeine ingestion improved exercise performance by comparable magnitudes.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Peak power output and mean power output were not significantly different during the trials in which caffeine or coffee was consumed when compared to the placebo and control trials. In contrast, Trexler et al [ 22 ] reported that caffeine and coffee ingestion improved sprint performance; however, a dose of 300 mg caffeine was ingested in this study and therefore participants will have consumed differing amounts of caffeine relative to their body mass. Similarly, Hodgson, Randell and Jeukendrup [ 21 ] observed that coffee and caffeine ingestion improved exercise performance by comparable magnitudes.…”
Section: Discussionmentioning
confidence: 63%
“…Crowe, Leicht and Spinks [ 35 ] suggest that the training status of participants has a substantial effect on short-term high-intensity performance. Therefore, it could be suggested that caffeine enhances performance in studies involving trained participants only, which has been observed by Schneiker et al [ 26 ] and others [ 2 , 3 , 4 , 22 ]. Collomp et al [ 36 ] suggested that specific training may be required to elicit ergogenic benefits from caffeine; improved performance in trained 100 m swimmers was observed following caffeine supplementation, but this improvement was not seen in untrained swimmers.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Kahve veya susuz tüketilen kuru kahvenin anaerobik aktivitelerdeki etkileri submaksimal egzersizlerdeki etkileri kadar net ortaya konulmamış olmasına rağmen kahve tüketiminin (0,09 g/kg) antrenmanlı erişkin erkeklerde 1,6 km koşu performansında artış sağladığı, kuvvet antrenmanlı erişkin erkeklerde kahve tüketiminin (8,9 g çözünebilir kahve yaklaşık 303 mg kafein) tekrarlı anaerobik performansı artırdığı ve bu amaçla uygun bir kafein kaynağı olabileceği önerilmiştir. 24,65,67 Bunun aksine aktif erişkin erkeklerde çözünebilir kahve tüketiminin anaerobik güç çıktısına ve 800 m koşu performansına etkisi olmadığını gösteren çalışmalar da vardır. 68,69 Farklı formlarda hazırlanmış kahvenin performansa etkilerinin araştırıldığı çalışma örneklerinde Türk usulü hazırlanan kahvenin (3 mg/kg) 5 km performansında artış sağladığı, bunun aksine ise 2 haftalık düzenli Türk kahvesi tüketiminin (474 mg kafein), 50 km bisiklet performansına etkisinin olmadığı da belirtilmiştir.…”
Section: Discussionunclassified
“…Hodgson et al [ 151 ] reported that both caffeine and coffee, standardized to deliver a caffeine dose of 5 mg/kg, were similarly efficacious in enhancing performance above placebo in a cycle ergometer test. Two studies [ 164 , 165 ] compared the use of coffee and caffeine anhydrous for their ergogenic effects on strength and sprint performance, reporting similar ergogenic effects for both modalities. These results suggest a similar ergogenic effect of both caffeine and coffee, provided the caffeine dose is matched.…”
Section: What Else Do We Need To Know About Caffeine In Sport?mentioning
confidence: 99%